النامي في العراق Eremostachys Bunge ( Labiatae ) دراسة تصنيفية حول الجنس - البياتي ميسون (Iraqi Journal of Science, 2025)
The research is a systematical study of gross morphology and pollen of plants – which collected during field trips and dry ones for most specimen preserved with the Iraqi herbaria –related to the genus Eremostachys Bunge and to identify the unidentified species and rectify the error there in .In the light of that the species of the genus in Iraq were specified in the two species : E.laciniata ( L.) Bunge and E.macrophylla Mont. & Auch.Characteristics of a taxonomic value have been specified for the genus and the two species which has not been mentioned before.Pollen were of a tricolpate and of medium size in the two species , but they showed several changes in there shapes , E.laciniata had the semi spherical shape in the polar view and its surface design an a fine reticulate but it is spherical and a finer reticulate in the other species . As for the equatorial view , it was eleptical in both species .The smaller one was noticed in E.macrophylla .The ecological and soil quality where these genus plants grows were specified ; and were geographically distributed on natural Iraqi territories for each one. Sketches and diagrams were made in addition to pictures .